2018
DOI: 10.3390/metabo9010004
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomics and Age-Related Macular Degeneration

Abstract: Age-related macular degeneration (AMD) leads to irreversible visual loss, therefore, early intervention is desirable, but due to its multifactorial nature, diagnosis of early disease might be challenging. Identification of early markers for disease development and progression is key for disease diagnosis. Suitable biomarkers can potentially provide opportunities for clinical intervention at a stage of the disease when irreversible changes are yet to take place. One of the most metabolically active tissues in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 237 publications
(300 reference statements)
2
40
0
Order By: Relevance
“…Thirdly, current prediction models do not include molecular risk factors, while these factors can be measured quantitatively . Because some molecular risk factors are potentially modifiable, this could help to implement personalised preventive strategies for AMD.…”
Section: Future Prediction Modelsmentioning
confidence: 99%
“…Thirdly, current prediction models do not include molecular risk factors, while these factors can be measured quantitatively . Because some molecular risk factors are potentially modifiable, this could help to implement personalised preventive strategies for AMD.…”
Section: Future Prediction Modelsmentioning
confidence: 99%
“… 2 The early stage of AMD has no obvious clinical symptoms and is not easy to detect. The advanced stage of AMD develops into two subtypes with different characteristics, including geographical atrophy (GA) and wet age-related macular degeneration, 3 , 4 leading to irreversible loss of vision. Studies have found that AMD has an obvious familial genetic predisposition, 5 and the genetic variation located at the complement factor H and ARMS2/HTRA1 sites has a great risk effect.…”
mentioning
confidence: 99%
“…It discloses anti-oxidant and anti-glycating properties [22] and was shown to be protective against aging and neurodegenerative diseases [23]. As increased oxidative stress and advanced glycation end products featuring AMD retina [6], it is tempting to speculate that the relative deficiency in carnosine could contribute to AMD pathogenesis. Since acetylcarnosine has been proposed as treatment in cataract and AMD a decade ago [24], we have carefully verified and excluded the consumption of acetylcarnosine and carnosine by patients and controls.…”
Section: Discussionmentioning
confidence: 99%
“…The few metabolic studies previously performed in AMD patients were recently reviewed [6]. A first study was performed using untargeted mass spectrometry in the plasma of neovascular AMD patients (n = 26) compared to controls (n = 19).…”
Section: Introductionmentioning
confidence: 99%